Estimation of Green Fodder Production and Availability in The Central Zone of Punjab - Amarpreet Kaur; Poonam Kataria; Avneet Kaur (Indian Journal of Animal Nutrition, 2025)
The paper estimates the green fodder production and availability in Ludhiana district using primary data from 90 farmers spread over standard land holding categories. The study revealed that out of green fodder production of 656.8 q/farm, 110.5q (constituting 17.2 % of maize, 28.2 % of sorghum, 21.9 % of pearl millet, 17.2 % of maize and 13.8 % of berseem produced) has been sold and remaining 546.3 q was available for feeding purposes. The availability of green fodder as per cent of production has been enumerated as 95 per cent (382.3 q) in case of small, 89.8 per cent (539.6 q) in case of medium and 76.3 per cent (663.1 q) in case of large farms. During summer and rainy season, the farmers fed their animals mainly pearl millet and maize while berseem was the most commonly fed fodder crop during winters. There was no significant difference between the green fodder availability (fresh basis) in rainy and winter season but the green fodder availability (DM basis) in summer and winter season was statistically lower than that in rainy season. Due to high percentage of dry matter in maize (23.3 %) and pearl millet (19.4 %), proportion of dry matter in roughage during rainy and monsoon season was more in comparison to that in summer and winter, when berseem (with 12.5 % dry matter) is primarily fed to the animals.